2005
DOI: 10.1016/j.orthres.2004.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Detection of changes in articular cartilage proteoglycan by T magnetic resonance imaging

Abstract: The purpose of this work is to demonstrate the feasibility of TI,,-weighted magnetic resonance imaging (MRI) to quantitatively measure changes in proteoglycan content in cartilage. The TI, MRI technique was implemented in an in vivo porcine animal model with rapidly induced cytokine-mediated cartilage degeneration. Six pigs were given an intra-articular injection of recombinant porcine interleukin-1 p (IL-1 p) into the knee joint before imaging to induce changes in cartilage via matrix metalloproteinase (MMP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 38 publications
3
66
2
1
Order By: Relevance
“…This is completely in conflict with several results from IL-1b studies on a larger group of samples and on an in vivo animal model where a significant increases in T 1r ( Figure 25) were observed (54,177). (3) At the higher field (8.5 T), T 1r should be lower than that at 1.5 T, but the T 1r numbers measured in human cartilage in this study are almost 50% higher than those observed at 1.5 T. This result was not explained.…”
Section: Experimental T 1r Studiescontrasting
confidence: 93%
See 3 more Smart Citations
“…This is completely in conflict with several results from IL-1b studies on a larger group of samples and on an in vivo animal model where a significant increases in T 1r ( Figure 25) were observed (54,177). (3) At the higher field (8.5 T), T 1r should be lower than that at 1.5 T, but the T 1r numbers measured in human cartilage in this study are almost 50% higher than those observed at 1.5 T. This result was not explained.…”
Section: Experimental T 1r Studiescontrasting
confidence: 93%
“…Genetic evidence for a role of IL-1b in OA came much more recently with the discovery of polymorphisms in the IL-1 gene cluster that act as risk factors for OA (51)(52)(53). In arthritis imaging research, IL-1b is now used to simulate osteoarthritis in animal models in order to track progression of mild disease by emerging techniques (54).…”
Section: Models Of Osteoarthritis In Articular Cartilagementioning
confidence: 99%
See 2 more Smart Citations
“…Other techniques, including delayed gadoliniumenhanced and sodium magnetic resonance imaging, may have sufficient sensitivity but there are also substantial limitations with regard to implementation of these methods [9][10][11] . T1r-weighted imaging is a spin-lock magnetic resonance imaging technique that shows promise as a noninvasive biomarker, as several in vivo studies have demonstrated the clinical feasibility of evaluating both intervertebral disc and articular cartilage with this modality [12][13][14][15] . The spin-lock technique was first employed by Redfield in 1955 and allows for a lower Larmor frequency 16 .…”
mentioning
confidence: 99%